A LITERATURE SURVEY ON RELATIONSHIP BETWEEN RENEWABLE ENERGY CONSUMPTION AND ECONOMIC GROWTH - Cvijović, Jelena; Obradović, Tijana; Knežević, Snežana Pavle (Economics of Agriculture, 2020)
The purpose of this paper is to provide an extensive empirical literature review on the relation between renewable energy consumption and economic growth. The survey included 50 papers, most of which are published in major energy journals, to ensure the high-quality review. This literature review includes period, countries, methodology and research results. Also, the survey included policy recommendation for renewable energy policymakers depending on results obtained by authors. The general observation from reviewed literature is the absence of any clear consensus regarding the relationship between renewable energy and economic growth, which can be contributed to various factors.